PENGARUH KARAKTER EKSEKUTIF, PROFITABILITAS, SALES GROWTH DAN CORPORATE SOCIAL RESPONSBILITY TERHADAP TAX AVOIDANCE PADA PERUSAHAAN NON-KEUANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2011-2015 - Rizki, M. Qyas Aulia; Fuadi, Raida (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2019)
The source of state revenue that has a large contribution in financing government spending is obtained from taxes. Taxes are levies which can be imposed on taxpayers, both entities and individuals based on tax laws. This study entitled